Earnings Management Following Duality-Creating Successions: Ethnostatistics, Impression Management, and Agency Theory - Davidson, Wallace N.; Jiraporn, Pornsit; Kim, Young Sang; Nemec, Carol (Academy of Management Journal, 2004)
We explore impression and earnings management via reasoning and methods grounded in ethnostatistics and agency theory. We hypothesized that earnings management occurs more frequently following duality-creating successions than otherwise because CEO-chairs have greater control of the impressions created by their firms' financial reports and are operating under greater expectations of positive results. Using a sample of 173 duality-creating succession announcements and 112 non-duality-creating succession announcements, we obtained empirical results consistent with these predictions.